LA TRANSMICION VERTICAL DEL VIH / SIDA EN MUJERES EMBARAZADAS DEL CANTON BABAHOYO EN EL AÑO 2006. - CARLOS PAZ SANCHEZ (2008)
THE VERTICAL TRANSMISSION OF HIV/AIDS IN PREGNANT WOMEN IN THE CANTON BABAHOYO IN THE YEAR 2006.